Swallowing Analyses of Neonates and Infants in Breastfeeding and Bottle-feeding: Impact on Videofluoroscopy Swallow Studies - Hernandez, Ana Maria; Bianchini, Esther Mandelbaum Gonçalves (International Archives of Otorhinolaryngology, 2019)
Introduction Dysphagia, when left untreated, can result in an increase in morbidity and mortality rates, especially among infants with history of life-threatening neonatal diseases. The videofluoroscopy swallowing study (VFSS) is considered the gold standard for the diagnosis of dysphagia. There are few imaging studies of infant swallowing based on videofluoroscopy, none of which were performed during breast-feeding.Objective To analyze the similarities and differences in infant swallowing function –regarding the feeding method – breast or bottle – and the impact on videofluoroscopy findings.Methods A retrospective study of 25 VFSSs of breastfeeding and bottle-feeding infants was performed. The studied variables were: oral capture and control; tongue versus mandible movement coordination; sucking pattern; mandible excursion; liquid flow; bolus retention; laryngeal penetration; tracheal aspiration; clearing of material collected in the pharynx; and gastroesophageal reflux (GER).Results The study showed a statistically significant association between nipple/areole capture; oral control; sucking pattern; mandibular excursion; liquid flow and feeding method. The velar sealing deficit, the place that trigger the pharyngeal swallow, food retention in the pharyngeal recesses, laryngeal penetration and GER were also factors associated with the feeding method.Conclusion The analysis of the swallowing characteristics of both feeding methods revealed significant differences between them, with an impact on the diagnosis in the VFSSs, especially regarding velar function.
Keywords: swallowing; dysphagia; neonates; infants; fluoroscopy; diagnosis